Expert radio system for Zimbabwe Broadcasting Holdings - Manjombo, Honest Kudakwashe (Midlands State University, 2019)
This study sought to craft an Expert Radios System for Zimbabwe Broadcasting Holdings. The researcher’s problem statement indicated that Zimbabwe Broadcasting Holdings is engaged in two media services namely television and radio broadcasting services, and the processes involved in their radio broadcasting was mainly through analogy radio signals. As technology evolves, the equipment currently in use becomes obsolete and makes it hard to keep maintaining available infrastructure to serve the population. In the research carried out, the objectives of the Expert Radio System were to schedule music playlist according to preference, filter program content according to profile, to publish listener advertisements, to publish news online, to promote artist music and to award royalties to most streamed music and programs. In order to meet these stated objectives, the business value to accrue from the Expert Radio System was noted and a feasibility analysis was performed and yielded positive results. Several risks associated to the ERS’s development were identified and counter measures were put in place. Stakeholder analysis identified system users, their expectations and interests in the new system and a work plan was drafted. Information gathering tools were used, namely, questionnaires, interviews and observations. Questionnaires were issued personally and interviews were conducted and results were documented for further assessment. Process and data analysis were performed on the previously implemented radio system and the system data flows were drawn. Weakness to the system were noted, alternatives for system development were evaluated and requirements analysis was done. In-house development was chosen as the development alternative for the new system. Designs for the Expert Radio System were drawn highlighting the data flows, architectural design, interface design, database table relationships and the system security designs. Implementation of the Expert Radio System was successfully done through performing code debugging, a series of test cases, and installation of the system. Recommendations to further develop the Expert Radio System was made for maintenance of network, security and system upgrades. A user manual and system installation instructions were provided.